Filozofia w poszukiwaniu tego, co niezmienne - Dewey, John (Hybris, 2007)
Rozdział drugi The Quest for Certainty. A Study of the Relation of Knowledge and Action. (Gifford Lectures 1929). Capricorn Books, New York 1960, ss. 26-48.